Edukasi Ketahanan Keluarga Berbasis Agama Islam Di Desa Banyuraden - Muthmainnah, Muthmainnah; Sobirin, Sobirin; Rahman, Ahmad Syafii; Arifin, Zainul; Riwaldi, Riwaldi (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2024)
The high and evenly distributed number of early marriages in Banyuraden Village, Gamping District, Sleman Regency should raise concerns in order to lessen the issue of family discord by bolstering the spiritual principles of Islam, which is the predominant religion practiced by the locals. One way to do this is by participating in one of the Toddler Family Development (Bina Keluarga Balita) activity groups. For this reason, Participation Action Research (PAR) was used to teach family resilience and conduct community service projects with pertinent themes. Planning, licensing, and communicating family resilience challenges are all part of the implementation at the BKB community group in the same village, Mutiara Hati Child Care Center. Additionally, a focus group discussion (FGD) was conducted about the creation of Islamically oriented family resilience materials associated with the BKB activities. The evaluation process is then preceded by socialization. The strengthening of Islamic-based family resilience materials that have been modified for BKB activities can still be done after completing this PKM activity.